Is angiotensin I-converting enzyme I/D polymorphism associated with endurance performance and/or high altitude adaptation? - Ohno, H.; Kizaki, T.; Suzuki, K.; Hitomi, Y.; Nakano, N.; Sakurai, T.; Ogiwara, R.; Sakirai, T.; Izawa, T.; Noguchi, I.; Nagasawa, J.; Ohnuki, Y.; et al. (Advances in Exercise and Sports Physiology, 2005)
It has been suggested that individual variations in human physical performances reflect both environmental factors and genetic element interaction. The report submitted by Montgomery et al. (Nature 393: 221-222, 1998) that, among climbers who had ascended beyond 8,000 m without supplemental inspired oxygen, non was of angiotensin I-converting enzyme (ACE) D/D genotype, gave not a few mountaineers a great impact. After that, the study on the influence of the ACE I (insertion)/D (deletion) polymorphism upon physical performance has become popular in the world. Collectively, the current review shows that it seems likely that the I allele is associated with enhanced endurance performance at high altitude as well as at sea level, via a local muscle effect rather than a central cardiorespiratory mechanism, attributable to the reduced angiotensin II and increased bradykinin, and that the D allele is associated with power-oriented athletic performance, via an angiothensin II-mediated increase in muscle growth and strengh, these being more apparent bin elite athletes.